Induction and Growth Kinetics Callus of Tomato (Solanum lycopersicum) - Arkan Setiaji; RR Rifka Annisa; Rumiyati Rumiyati; Endang Semiarti (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Plant callus extracts are potential to be developed as ingredient in skincare products. Tomato callus is supposed to contain protein-derivatives and or other components such as secondary metabolites that play a role in skin regeneration. Therefore the production of calli is important to be studied for callus sustainable supply. This research aims to obtain optimum medium for callus induction and to analyze tomato callus development anatomically. In vitro culture response was assessed in tomato plant (Solanum lycopersicum L. ‘Permata’) for optimum callus induction. Seeds were grown on ¼ MS medium for 10-15 days. Hypocotyl was excised and cultured on MS medium + 2 mg/l 2,4-D for 15 days as the explants for callus induction. Callus was transferred to MS medium with 8 variations of PGRs including the combination of BAP + NAA, and 2,4-D. Both fresh and dry weight was measured every 5 days over 60 days to establish the growth kinetics and growth efficiency of callus. Anatomic characters of calli were examined through paraffin-embedded method. The result showed of MS medium supplemented with 2.0 mg/l NAA and 0.2 mg/l BAP is optimum for tomato callus induction, based on highest number of the absolute growth rate on fresh weight (73.77% per day), dry weight (3.84% per day), and callus initiation time (5.56 days) achieved by the medium. Cells in the ground tissue of tomato hypocotyl are competent to be dedifferentiated into a callus. This research results were expected to find out suitable methods for tomato callus production in preparation for skincare uses.